Synthesis and interaction of bovine serum albumin with p‐hydroxybenzoic acid derivatives. (24th July 2012) - Zhang, Xue‐Hong; Liu, Li‐Na; Lin, Yi‐Jie; Lin, Cui‐Wu
ABSTRACT: Three novel p‐hydroxybenzoic acid derivatives (HSOP, HSOX, HSCP) were synthesized from p‐hydroxybenzoic acid and sulfonamides (sulfamonomethoxine sodium, sulfamethoxazole and sulfachloropyridazine sodium) and characterized by elemental analysis, HNMR and MS. Interactions between derivatives and bovine serum albumin (BSA) were studied by fluorescence quenching spectra, UV–vis absorption spectra and time‐resolved fluorescence spectra. Based on fluorescence quenching calculation and Förster's non‐radioactive energy transfer theory, the values of the binding constants, basic thermodynamic parameters and binding distances were obtained. Experimental results indicated that the three derivatives had a strong ability to quench fluorescence from BSA and that the binding reactions of the derivatives with BSA were a static quenching process. Thermodynamic parameters showed that binding reactions were spontaneous and exothermic and hydrogen bond and van der Waals force were predominant intermolecular forces between the derivatives and BSA. Synchronous fluorescence spectra suggested that HSOX and HSCP had little effect on the microenvironment and conformation of BSA in the binding reactions but the microenvironments around tyrosine residues were disturbed and polarity around tyrosine residues increased in the presence of HSOP. Copyright © 2012 John Wiley & Sons, Ltd.